The role of X-inactivation in the gender bias of patients with acquired alpha-thalassaemia and myelodysplastic syndrome (ATMDS). - Haas, P; Roy, N; Gibbons, R; Deville, M; Fisher, C; Schwabe, M; Bissé, E; van Dorsselaer, A; Higgs, D; Lübbert, M (2009)
Alpha thalassaemia myelodysplastic syndrome (ATMDS) is an unusual complication of chronic myeloid malignancy that is associated with a striking red cell phenotype. It represents an acquired form of alpha-thalassaemia that most commonly arises in the context of myelodysplasia. It has recently been shown that this condition occurs in association with somatic mutations of a known X-encoded trans-acting regulator of alpha globin gene (HBA) expression, ATRX. There is an unexplained, strong male preponderance of individuals with the ATMDS phenotype with a >5:1 male-female ratio and furthermore, all the somatic ATRX mutations described to date have been in males. Here we report the identification, in a single centre, of two females with ATMDS and mutations in the ATRX gene, proving that ATMDS associated with such mutations may occur, albeit rarely, in females. It seemed possible that females might be less likely to develop ATMDS if the inactivated copy of the ATRX gene (ATRX) became progressively re-activated throughout life. This study ruled out this hypothesis by investigating the pattern of ATRX inactivation in a cross-sectional analysis of normal females at ages ranging from newborn to 90 years.